The three sector solution : delivering public policy in collaboration with not-for-profits and business - Gilchrist, David; Butcher, John (ANZSOG (Series), 2016)
"This collection of essays had its origins in a one-day workshop held in August 2015 at The Australian National University. Jointly convened by Dr John Butcher (ANZSOG) and Professor David Gilchrist (Curtin Not-for-profit Initiative) the purpose of the workshop was to bring together academic researchers, policy practitioners and thought leaders to address a variety of emerging issues facing policymakers, public sector commissioners, not-for-profit providers of publicly funded services, and businesses interested in opportunities for social investment. The workshop itself generated a great deal of interest and a 'baker's dozen' of contributors challenged and engaged a full house. The level of enthusiasm shown by the audience for the subject matter was such that the decision to curate the presentations in the form of a book was never in doubt. The editors trust that this volume will vindicate that decision. At one time the state exercised a near monopoly in the delivery of social programs. Today, almost every important public problem is a three sector problem and yet we have little idea of what a high-performing three sector production system looks like. It is the editors' hope that this volume will provide a foundation for some answers to these important public policy questions"--Provided by publisher.